2011
DOI: 10.1021/am200590w
|View full text |Cite
|
Sign up to set email alerts
|

PEMFC Catalyst Layers: The Role of Micropores and Mesopores on Water Sorption and Fuel Cell Activity

Abstract: The effects of carbon microstructure and ionomer loading on water vapor sorption and retention in catalyst layers (CLs) of PEM fuel cells are investigated using dynamic vapor sorption. Catalyst layers based on Ketjen Black and Vulcan XC-72 carbon blacks, which possess distinctly different surface areas, pore volumes, and microporosities, are studied. It is found that pores <20 nm diameter facilitate water uptake by capillary condensation in the intermediate range of relative humidities. A broad pore size distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
178
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 187 publications
(184 citation statements)
references
References 31 publications
(51 reference statements)
4
178
0
2
Order By: Relevance
“…As shown in Figure 20, water-uptake isotherms for Nafion in the catalyst layers show much lower water contents compared to bulk Nafion membrane. 157 Also, water uptake in catalyst layers has been shown to increase with increasing loading of platinum, which improves wetting properties and hydrophilicity, 157,326 and with increasing ionomer content, 326,327 although in general the catalyst layer's ionomer water uptake has been consistently shown to be depressed. 157,327 With the lower water contents (and perhaps the existence of different morphology and confinement driving the lower water uptake), it is not surprising that the ion conductivity is likewise depressed, [327][328][329] and is a function of ionomer content.…”
Section: Catalyst-layer Modelingmentioning
confidence: 99%
“…As shown in Figure 20, water-uptake isotherms for Nafion in the catalyst layers show much lower water contents compared to bulk Nafion membrane. 157 Also, water uptake in catalyst layers has been shown to increase with increasing loading of platinum, which improves wetting properties and hydrophilicity, 157,326 and with increasing ionomer content, 326,327 although in general the catalyst layer's ionomer water uptake has been consistently shown to be depressed. 157,327 With the lower water contents (and perhaps the existence of different morphology and confinement driving the lower water uptake), it is not surprising that the ion conductivity is likewise depressed, [327][328][329] and is a function of ionomer content.…”
Section: Catalyst-layer Modelingmentioning
confidence: 99%
“…• by considering the contact angle of Ketjen Black carbons reported by Soboleva et al 45 All electrochemical parameters for CLs are obtained from the experiments discussed in the MEA fabrication and testing section in a follow up article. 46 The thermal related parameters, i.e., GDLs, CLs and PEM thermal conductivity as well as all PEM transport properties used in the model are from the previous OpenFCST non-isothermal MEA model validation study reported by Bhaiya et al 20 The double trap and dual path kinetic parameters used in the model are given in Moore et al 22 and Wang et al, 47 respectively.…”
Section: F532mentioning
confidence: 99%
“…To achieve this, we adapted the ultrasonic spray-coating technique to AEMFCs in order to probe the effect of high-boiling solvents in catalyst layer formation, characterizing the resultant CCMs in situ, in AEMFCs, and ex situ using porosimetry and scanning electron microscopy, contextualizing these results with relevant electrochemical data, as in previous PEMFC studies by our group. 34,35 No true benchmark for AEMFC function has yet been established, but FAA-3 represents one of the few high-performance anion-exchange ionomers and unreinforced membranes commercially available, and is the subject to the most extensive parametric studies to date. 36 Consequently, we chose these materials to undertake studies of structure-property relationships of catalyst layers.…”
Section: F354mentioning
confidence: 99%